Cullin-RING ligases in regulation of autophagy. Issue 1 (March 2016) - Cui, Danrui; Xiong, Xiufang; Zhao, Yongchao
Abstract Cullin-RING ligases (CRLs), the largest E3 ubiquitin ligase family, promote ubiquitination and degradation of various cellular key regulators involved in a broad array of physiological and pathological processes, including cell cycle progression, signal transduction, transcription, cardiomyopathy, and tumorigenesis. Autophagy, an intracellular catabolic reaction that delivers cytoplasmic components to lysosomes for degradation, is crucial for cellular metabolism and homeostasis. The dysfunction of autophagy has been proved to associate with a variety of human diseases. Recent evidences revealed the emerging roles of CRLs in the regulation of autophagy. In this review, we will focus mainly on recent advances in our understandings of the regulation of autophagy by CRLs and the cross-talk between CRLs and autophagy, two degradation systems. We will also discuss the pathogenesis of human diseases associated with the dysregulation of CRLs and autophagy. Finally, we will discuss current efforts and future perspectives on basic and translational research on CRLs and autophagy.